2006
DOI: 10.1007/s11916-006-0075-2
|View full text |Cite
|
Sign up to set email alerts
|

Tension-type headache and psychiatric comorbidity

Abstract: Much of the contemporary literature on headache disorders focuses on migraine headaches, despite the fact that tension-type headache (TTH) is highly prevalent and can be as debilitating as migraines. This article reviews the current literature on prevalence rates of psychiatric disorders in TTH populations, psychologic factors associated with TTH, and psychiatric disorders and their relationships with treatment outcomes in TTH. Key conclusions of this review include 1) prevalence rates of TTH vary across clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 54 publications
1
29
0
1
Order By: Relevance
“…In the current study, we also found that both anxiety and depression levels were higher in CTTH and MOH, which is consistent with previous reports [24][25][26][27][28]. Moreover, age correlates with the line bisection errors found in the current study were consistent with many previous reports [17], implying an age-related and right-(facial decision task) hemispheric dominant tasks [41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, we also found that both anxiety and depression levels were higher in CTTH and MOH, which is consistent with previous reports [24][25][26][27][28]. Moreover, age correlates with the line bisection errors found in the current study were consistent with many previous reports [17], implying an age-related and right-(facial decision task) hemispheric dominant tasks [41].…”
Section: Discussionsupporting
confidence: 93%
“…In order to exclude the effect of chronic head pain, we have included a group of patients with CTTH. Bearing in mind that patients with generalized anxiety disorder bisected lines significantly leftward [23], and that both anxiety and depression are comorbid with MOH [24,25] and CTTH [26][27][28], we have used the Zung Self-Rating Anxiety Scale [29] and the Zung Self-Rating Depression Scale [30] to measure the anxiety and depression levels in our participants. the Zung 20-item Self-rating Anxiety Scale [29].…”
Section: Introductionmentioning
confidence: 99%
“…Although the lines of study may differ, there seems to be agreement that these conditions overlap with anxiety, depression, maladaptive coping, inability to communicate with others and deal with life events, and common pathophysiological origins 7,[19][20][21][22][23][24][25] . The results from the present study further add to the discussion on the very high prevalence of signs and symptoms of TMD among primary headache patients.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that the one-year prevalence rate of TTH changes during adulthood and that TTH is a dynamic condition [48,49]. For instance, rates of TTH increased from 79% to 87% over a 12-year period among young adults in Denmark [7].…”
Section: Tth As a Dynamic Conditionmentioning
confidence: 99%
“…Researchers have identified multiple precipitants and correlates of TTH [48]. The most frequently reported precipitants of TTH are stress or mental tension [5], followed by sleep problems or fatigue [52].…”
Section: Precipitants and Correlates Of Tthmentioning
confidence: 99%